Beyond A Common Infection: Comprehensive Oral Management Strategies For Severe Recurrent Intraoral Herpes - Imme Kris Wicaksono; Cindy Karina Hartono; Ivan Djuarsa; Bernadeth Vindi Januarisca (Jurnal Medali, 2026)
Background: Recurrent intraoral herpes (RIH) is caused by reactivation of Herpes Simplex Virus type 1 (HSV-1). While HSV-1 infection is usually self-limiting, severe cases requiring hospitalization are uncommon and present significant clinical challenges. Delayed diagnosis or inadequate antiviral therapy can contribute to disease progression and increased morbidity.This case study aims to illustrate an effective therapeutic approach for managing severe RIH in a patient presenting with intense pain and difficulty swallowing, emphasizing strategies that enhance patient comfort and improve clinical outcomes.Case: An 24-year-old male presented in a markedly weakened condition with severe difficulty swallowing. Examination revealed multiple ulcerative lesions of varying sizes diffusely throughout the oral cavity, with extensive erythema and severe pain (Visual Analog Scale [VAS] score: 8). Vital signs at presentation were blood pressure 90/60 mmHg and oxygen saturation 91%. Due to his weakened state and significant pain, inpatient care was required for close monitoring and nutritional support.Treatment included systemic acyclovir 400 mg, multivitamins, 0.025% hyaluronic acid mouthwash, 0.9% saline, and petroleum jelly 100%. After seven days of therapy, the patient clinically improved. Lesions gradually decreased in size, number, erythema subsided, and pain significantly reduced, allowing resumption of oral intake. VAS score decreased from 8 at admission to 5 at discharge. Conclusion:Severe RIH can necessitate hospitalization and multidisciplinary management. Early initiation of systemic antiviral therapy combined with supportive care effectively reduces symptoms, improves nutritional intake, and prevents further deterioration. Timely, comprehensive intervention is critical for optimal outcomes in severe HSV-1 reactivation.